Mentoring sebagai percakapan mendalam untuk menemukan panggilan menjadi pendeta - Munster, Cindy Cecilia Tumbelaka-van; Dawa, Mariani Febriana Lere (Sekolah Tinggi Teologi Pelita Bangsa, Jakarta, 2024)
This article is about the church's mentoring process for those who become her prospective pastors. There is a tendency for this mentoring process to be more directed towards coaching, where the church conveys more information that the prospective new pastor needs to pay attention to. However, mentoring requires a more profound vision to approach a minister, not only coaching but also a journey of inner clarity to understand better and experience the reality of